2016
DOI: 10.1016/j.habitatint.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and administrative restructuring: A case study on the Wuhan urban agglomeration

Abstract: a b s t r a c tUrbanization in China has been closely associated with urban sprawl, rural migration and the role of government has been more direct and powerful in setting it in motion. In 2014, the New Urbanization Planning in China has been released in which the development of urban agglomeration and smallmedium cities has been highlighted. In this context, we decompose urbanization into populationoriented and land-centered archetypes and devise spatial models in multiple strategies embedded with different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Besides the well-developed ground transportation system, several subways have been constructed and are operational. Surrounded by many seaways, expressways, and railways, the city is practically one of the transportation hubs of China [41,42]. The well-developed urban infrastructure of the city has attracted a significant number of residents, including many students that graduated from universities, to settle down here after migrating from the nearby satellite cities as well as other cities across the country.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the well-developed ground transportation system, several subways have been constructed and are operational. Surrounded by many seaways, expressways, and railways, the city is practically one of the transportation hubs of China [41,42]. The well-developed urban infrastructure of the city has attracted a significant number of residents, including many students that graduated from universities, to settle down here after migrating from the nearby satellite cities as well as other cities across the country.…”
Section: Study Areamentioning
confidence: 99%
“…The vegetative areas are the most direct frontier that interacts with land exploitation. Therefore, the changes of vegetation space in the city has gained more consideration from the local government and urban planners than ever before [42]. Figure 1d Our interest was to explore the changes in urban greenness associated with the urbanization process, therefore a radius of 50 km centered at the urban center, referred to as the region of interest (ROI), including the downtown area, part of the suburban districts, and part of a few satellite cities around the megacity, was selected as the study region ( Figure 1c).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Land-use changes in Wuhan, China, in (Zeng et al 2015a) and (Sun et al 2016) revealed a general deterioration in vegetation cover and growth of impervious areas for the expansion of residential areas over most of the period from 1991 to 2013. In (Zeng, Zhang, and Xu 2016) some of the driving forces for the rapid urbanization in Wuhan have been listed as: urban sprawl; rural migration; socio-economic and transportation developments; and spatial interaction of counties that has been essential for realizing regional urbanization. In the study of changes in urbanization, change detection is often an essential task for decision-makers.…”
Section: Sustainability Of Urban Environmentsmentioning
confidence: 99%
“…The development of urbanization has always been an important issue in both ecological and socio-economic research [1][2][3][4][5][6]. The process of urbanization, which is intertwined with land cover transformation, has a direct and profound impact on changes in land use.…”
Section: Introductionmentioning
confidence: 99%